The interaction between autophagy and the epithelial-mesenchymal transition mediated by NICD/ULK1 is involved in the formation of diabetic cataracts - Jiyuan Ma; Wei Ye; Yunshu Yang; Tong Wu; Yafen Wang; Ji Li; Rui Pei; Mengmei He; Luning Zhang; Jian Zhou (BMC, 2022)
Abstract Background Cataracts are the leading cause of blindness and a common ocular complication of diabetes. The epithelial-mesenchymal transition (EMT) of lens epithelial cells (LECs) and altered autophagic activity occur during the development of diabetic cataracts. The disturbed interaction of autophagy with EMT in LECs stimulated by high glucose levels may participate in cataract formation. Methods A rat diabetic cataract model induced by streptozotocin (STZ) and human lens epithelial cells (HLE-B3) stimulated with a high glucose concentration were employed in the study. These models were treated with rapamycin (an inhibitor of mammalian target of rapamycin (mTOR)), and N-(N-[3,5-difluorophenacetyl]-1-alanyl)-S-phenylglycine t-butyl ester (DAPT, an inhibitor of γ-secretase) alone or in combination. Lens opacity was observed and photographed under a slit-lamp microscope. Histological changes in paraffin sections of lenses were detected under a light microscope after hematoxylin and eosin staining. Alterations of autophagosomes in LECs were counted and evaluated under a transmission electron microscope. The expression levels of proteins involved in the EMT, autophagy, and the signaling pathways in LECs were measured using Western blotting and immunofluorescence staining. Cell migration was determined by performing transwell and scratch wound assays. Coimmunoprecipitation (Co-IP) was performed to verify protein-protein interactions. Proteins were overexpressed in transfected cells to confirm their roles in the signaling pathways of interest. Results In LECs, a high glucose concentration induces the EMT by activating Jagged1/Notch1/Notch intracellular domain (NICD)/Snail signaling and inhibits autophagy through the AKT/mTOR/unc 51-like kinase 1 (ULK1) signaling pathway in vivo and in vitro, resulting in diabetic cataracts. Enhanced autophagic activity induced by rapamycin suppressed the EMT by inducing Notch1 degradation by SQSTM1/p62 and microtubule-associated protein light chain 3 (LC3) in LECs, while inhibition of the Notch signaling pathway with DAPT not only prevented the EMT but also activated autophagy by decreasing the levels of NICD, which bound to ULK1, phosphorylated it, and then inhibited the initiation of autophagy. Conclusions We describe a new interaction of autophagy and the EMT involving NICD/ULK1 signaling, which mediates crosstalk between these two important events in the formation of diabetic cataracts. Activating autophagy and suppressing the EMT mutually promote each other, revealing a potential target and strategy for the prevention of diabetic cataracts.